Almond protects the liver in coronary artery disease – a randomized controlled clinical trial - Humaira Jamshed; Jamshed Arslan; Fatehali Tipoo Sultan; Hasan Salman Siddiqi; Muhammad Qasim; Anwar-ul-Hassan Gilani; Admin (Journal of the Pakistan Medical Association, 2020)
Objective: To compare the effect of Pakistani and American almonds on serum concentration of liver enzymes in coronary artery disease patients. Methods: The randomised controlled trial was conducted at the Cardiology Clinics of Aga Khan University Hospital, Karachi, from February to July, 2012, and comprised patients who were randomised into intervention PA and AA groups and the control NI groups. Subjects in the intervention groups were provided Pakistani and American varieties of almonds 10g/day respectively with instructions to soak them overnight, remove the skin and eat them before breakfast for 12 weeks. The control group underwent no intervention. Serum concentrations of aspartate transaminase, Alanine transaminase and gamma-glutamyl transferase were analysed and compared. Results: Of the 150 subjects, 110(73.3%) completed the study. Of them, there were 38(34.5%) in PA group, 41(37.3%) in AA, and 31(28.2%) in the NI group. Dietary almonds significantly reduced serum concentrations of aspartate transaminase, alanine transaminase and gamma-glutamyl transferase in the two intervention groups compared to the controls group (p<0.05) at 12-week follow-up. Conclusion: A low dose of almonds was found to be an effective strategy to protect the liver. Key Words: Low dose, Soaked almonds, Transaminases, Transpeptidase, SGOT/SGPT. Continuous...